KOMUNITAS SABUNG AYAM: Studi Perilaku Menyimpang Masyarakat Malakaji Kabupaten Gowa - Arlin Adam (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2015)
The study aimed at examining the factors which cause cockfight as deviant behavior, describing the process of shifting of the function and meaning of cockfight as deviant behavior, describing the meaning of the work that the deviant behavior is coherent with the behavior of Malakaji people, and describing the approach to be conducted so cockfight behavior becomes comformity behavior. The study employed descriptive qualitative approach. The informants were taken by employing purposive sampling technique. The categories of informants used were key informant, experst and regular with various professions as businessman, employee, entrepreneur, handyman, driver, and farmer. The criterion of the informants was the ones who do the cockfight for 3 years. The results the study were (i) cockfight (assaung) is a deviant behavior because against the cultural value, religion, and law, (ii) cockfight is a deviant behavior gave implication on the shifting of the function and meaning, (iii) the function and meaning of cockfight as the object were interpreted by the community based on its social roles, and (iv) active functions of the elements of people as social control as deconstruction of cockfight meaning from deviant behavior is a conformity behavior to create regularity of Malakaji people in Gowa district.